The coupling effect of socio-economic and eco-environment and land use transformation in mountainous areas—a case of the Fengjie County in the Three Gorges Reservoir Area, China - Chunhua Xia; Yangbing Li; Jingan Shao; Shijie Yan; Yan Chen; Luoshan Zheng; Rong Wang (Environmental Science and Pollution Research, 2022)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Interaction of Amiodarone with Azoles Against Aspergillus Planktonic Cells and Biofilms in vitro - Zhimin Duan; Jianbo Tong; Nana Zheng; Rong Zeng; Yuzhen Liu; Min Li (Mycopathologia, 2022)

Design strategy of self-assembled BC@MIL-100(Fe) composite membrane for the efficient removal of diclofenac sodium from water - Rong Cheng; Weilong Li; Jinlin Wang; Jie Li; Jianzhong Zheng; Xiang Zheng (Environmental Science and Pollution Research, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Hao Kang; Yongxiang Yu; Meijie Liao; Yingeng Wang; Guanpin Yang; Zheng Zhang; Bin Li; Xiaojun Rong; Chunyuan Wang (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes ( gyrB , pyrH , recA , and atpA ), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yongxiang Yu; Xiao Liu; Yingeng Wang; Meijie Liao; Miaomiao Tang; Xiaojun Rong; Chunyuan Wang; Bin Li; Zheng Zhang (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro . Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5%~81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes ( strB , strA , ant(3 ˝)-I , mphA , blaPSE , qnrS , tetC , tetE , tetM , tetS , and int1 ) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

A low-cost in-situ CO2 sensor based on a membrane and NDIR for long-term measurement in seawater - Meng Li; Baolu Du; Jinjia Guo; Zhihao Zhang; Zeyu Lu; Rong’er Zheng (Journal of Oceanology and Limnology, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Synchronous removal of tetracycline and copper (II) over Z‑scheme BiVO4/rGO/g-C3N4 photocatalyst under visible-light irradiation - Jiangli Sun; Yiyuan Rong; Yanping Hou; Lingli Tu; Qingyu Wang; Yuying Mo; Shuxuan Zheng; Zan Li; Zuji Li; Zebin Yu (Environmental Science and Pollution Research, 2022)

Understanding the key factors determining rural domestic waste treatment behavior in China: a meta-analysis - Donghui Zheng; Jing Shen; Rong Li; Bei Jian; Jihong Zeng; Yongliang Mao; Xiaoning Zhang; Pradipta Halder; Mei Qu (Environmental Science and Pollution Research, 2022)